CCM3/SERPINI1 bidirectional promoter variants in patients with cerebral cavernous malformations: a molecular and functional study. Issue 1 (December 2016) - Scimone, Concetta; Bramanti, Placido; Ruggeri, Alessia; Donato, Luigi; Alafaci, Concetta; Crisafulli, Concetta; Mucciardi, Massimo; Rinaldi, Carmela; Sidoti, Antonina; D'Angelo, Rosalia
Abstract Background Cerebral cavernous malformations (CCMs) are vascular anomalies of the nervous system mostly located in the brain presenting sporadically or familial. Causes of familial forms are mutations inCCM1 (Krit1), CCM2 (MGC4607) andCCM3 (PDCD10) genes. Sporadic forms with no affected relative most often have only one lesion and no germ line mutations. However, a number of sporadic cases with multiple lesions have been reported and are indeed genetic cases with a de novo mutation or a mutation inherited from an asymptomatic parent. Methods Here, we performed an analysis of regulatory region of CCM genes in 60 sporadic patients, negative for mutations in coding region and intron-exon boundaries and large deletion/duplications in CCM genes by direct sequencing and MLPA. Among 5 variants identified in 851-bp region shared byCCM3 andSERPINI1 genes and acting as asymmetric bidirectional promoter, two polymorphisms c.-639 T > C/rs9853967 and c.-591 T > C/rs11714980 were selected. A case-control study was performed to analyze their possible relationships with sporadic CCMs. Promoter haplotypes activities onCCM3/SERPINI1 genes expression were tested by dual-luciferase assay. Results No variants were identified inCCM1 andCCM2 regulatory regions. InCCM3 /SERPINI1 asymmetric bidirectional promoter 5 variants, 2 of them unknown and 3 corresponding to polymorphisms c.-639 T > C/rs9853967, c.-591 T > C/rs11714980 and c.-359G > A/rs9834676 were detected. While rs9853967 and rs11714980 polymorphisms fall in a critical regulatory fragment outside the minimal promoter in intergenic region, other variants had no effects on transcription factor binding according to RegRNA tool. Case-control study performed on 60 patients and 350 healthy controls showed frequencies of the mutated alleles significantly higher in the control group than in patients. Furthermore, the functional assay showed a significant reduction ofCCM3 expression for C-C haplotype even more than for T-C and C-T haplotypes. InSERPINI1 direction, the reduction was not statistically significant. Conclusions Our data indicated that rs9853967 and rs11714980 polymorphisms could be associated with a protective role in CCM disease.